Structure of methanol sub-monolayer on functionalized graphite at temperatures below the triple point - Waralee Dilokekunakul (2020)
© 2019 Elsevier B.V. Grand canonical simulations were carried out to determine the microscopic structures of the sub-monolayer of methanol on a graphite model with two hydroxyl groups attached to the basal plane. At temperatures below the triple point temperature of methanol (176 K), the adsorption isotherm exhibits four distinct transitions: (1) saturation of the OH groups, (2) formation of 2D ring clusters floating on the basal plane, (3) transition to 2D string clusters with one end attached to the OH groups, and (4) compaction of the 2D string clusters. The variation in the molecular distribution and orientation for these transitions is studied, and correlated with the changes in isosteric heat across these transitions. It is found that the ring-to-string transition occurs more readily at low temperatures, and that the hydrogen bond length (O⋯H) within a ring or a string is constant.